The Transformation of Islamic Values Through Digital Comics: A Case Study at MTSn Pariaman - Utama, Yudi Nanda (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2024)
This study aims to explore the effectiveness of using digital comics as a learning medium in transforming and internalizing Islamic values at MTsN Pariaman. In the rapidly developing digital era, conventional teaching methods are often less able to attract the attention of students who grow up in a technological environment. Therefore, innovation in learning media is very important to increase student engagement and understanding. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with teachers and students, and analysis of documentation related to the use of digital comics in the classroom. The results of the study showed that digital comics were not only successful in increasing students' interest in learning, but were also effective in conveying moral messages and Islamic values in a more interactive and enjoyable way. Teachers at MTsN Pariaman reported that students found it easier to understand and remember material delivered through digital comics compared to traditional teaching methods.